KONTRUKSI MAKNA DIRI WARIA BAGI ANGGOTA KOMUNITAS TEATER MANEKIN DALAM PERSPREKTIF FENOMENOLOGI - Siti Rahma Wati; Ana Fitriana Poerana; Tri Susanto (JIKE: Jurnal Ilmu Komunikasi Efek, 2025)
This research aims to understand how transvestites shape their meaning through their experiences as members of the Mannequin Theater Community in Kampung Duri, West Jakarta. This community is a safe space for transvestites to express themselves and live a more inclusive social life. This study uses a qualitative approach with Alfred Schutz's phenomenological method to examine the subjective experiences of informants. Data was collected through observation and in- depth interviews with four transvestite community members. The results of the study showed that each informant had a different sense of self, such as the courage to be themselves, pride in identity, the desire to be useful to others, and the determination to live life according to personal choice. This sense of self is born from the process of interaction in the community that provides a safe space and social support for its members.